Single cell lipidomics of SKBR‐3 breast cancer cells by using time‐of‐flight secondary‐ion mass spectrometry. (30th April 2014) - Ide, Yoshimi; Waki, Michihiko; Ishizaki, Itsuko; Nagata, Yasuyuki; Yamazaki, Fumiyoshi; Hayasaka, Takahiro; Masaki, Noritaka; Ikegami, Koji; Kondo, Takeshi; Shibata, Kiyoshi; Ogura, Hiroyuki; Sanada, Noriaki; et al.
<x xml:space="preserve">Abstract</x> Breast cancer is the most common cancer among women worldwide. The molecular characterization of breast tumor cells by using single‐cell lipidomics remains relatively unexplored. Here, we introduce a time‐of‐flight secondary‐ion mass spectrometry (TOF‐SIMS) approach to visualize the lipids in individual breast cancer cells. The SKBR‐3 breast cancer cell line was cultured and dispersed into individual cells. After attachment to a substrate, the cells were rinsed with ammonium acetate and were analyzed using TOF‐SIMS. The instrument was operated with Bi32+ as the primary ion. The distributions of ions, including positively charged phosphocholine, and negatively charged phosphates and fatty acids, were simultaneously visualized. These ions were distributed predominantly at the cell attachment sites. The signal intensities of fatty acid ions were determined from the mass spectra at the regions‐of‐interest. The results of fatty acid analyses on breast cancer cells were consistent with those of our previous study in which prominent expression of stearoyl‐CoA desaturase 1 in breast cancer cells was demonstrated. Static TOF‐SIMS was shown to be an effective method for determining the lipid molecular signature of the plasma membrane of individual breast cancer cells. Copyright © 2014 John Wiley & Sons, Ltd.